Impact of Insulin Resistance on Complications of Pregnancy and Outcome in Women with PCOS - Sadaf Maqsood, Mehwish Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aimed to evaluate the risk of increasing gestational diabetes mellitus (GDM) and pregnancy-induced hypertension (PIH) among pregnant females that were suffering from polycystic ovarian syndrome (PCOS). The study compares a population of PCOS females with reported insulin resistance with those of a control population of females who are pregnant after receiving infertile therapy. Method: It was a cohort study and a purposive sampling technique had been used. Conceiving maternal outcomes were recorded in a prospective cohort study with 28 non-insulin-resistant and 24 insulin-resistant PCOS females and 354 females expecting after getting infertile reproduction therapy. Hypertensive and GDM were measured during pregnancy and delivery methods. Gestation period, and delivery technique, have all been noted along with hypertensive, pre-eclampsia, & GDM. Results: When contrasted to controls, PCOS females had a substantially higher frequency of hypertension (12.5%), with a p-value of 6! 0.01. Nevertheless, particularly insulin-resistant PCOS females (13.5%) experienced pre-eclampsia at a substantially higher rate than controls (7.1%), with a p-value of! 0.02. GDM occurred 7.8% more frequently in PCOS females compared in controls (0.7%), a considerable difference (p! 0.01). The prevalence of GDM had not been further increased by pre-pregnancy insulin resistance as measured by the continual administration of glucose with modeling evaluation (CIGMA) test. Critical prenatal nursing unit transfers and C - section deliveries were substantially more common for neonates from PCOS conceptions than for controls (44.3 vs. 26.3%, p! 0.05) as well as 19.3 vs. 8.0%, respectively. Conclusion: In conclusion, the study demonstrated that hypertension and GDM were more common in PCOS pregnant females. Keywords: Hypertension, gestational diabetes mellitus, insulin resistance, polycystic ovary syndrome